2000
DOI: 10.1366/0003702001948925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operating Frequency on Spatial Features of the Inductively Coupled Plasma

Abstract: An unambiguous comparison has been made of the spatial features of a 27.12 and a 40.68 MH z inductively coupled plasma. Experiments were carried out with a switchable-frequency, solid-state radio-frequency generator from the Leco 2000 system. Several features of analytical signi cance have been evaluated in a spatially resolved fashion. Resu lts from optimization of the magnesium ionto-atom (M g II/Mg I) line-intensity ratio have been com pared. The volume of the two discharges was estimated from molecular nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…6 Consistently, a reduction in the Mg II : Mg I ratio, an indication of plasma robustness, was later reported at 40 MHz for the same experimental system. 7 As in the ICP-AES investigations, the effect of the operating frequency on the analytical characteristics of ICP-MS systems has also been evaluated. 1,2 Optimal nebulizer flow rates for 40 MHz systems are typically lower than those at 27 MHz, and the axial distributions of analyte and background ions are shifted to lower sampling depths in 27 MHz plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…6 Consistently, a reduction in the Mg II : Mg I ratio, an indication of plasma robustness, was later reported at 40 MHz for the same experimental system. 7 As in the ICP-AES investigations, the effect of the operating frequency on the analytical characteristics of ICP-MS systems has also been evaluated. 1,2 Optimal nebulizer flow rates for 40 MHz systems are typically lower than those at 27 MHz, and the axial distributions of analyte and background ions are shifted to lower sampling depths in 27 MHz plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…218 A spatial comparison has been made of ICPs operated at 27.12 and 40.68 MHz using a switchable-frequency generator. 219 The Mg II/Mg I ratio, Fe I T exc and discharge volume (from N 2 ion emission) were studied. After optimisation the authors concluded that slightly better figures of merit were obtained with the 40.68 MHz ICP.…”
Section: Inductively Coupled Plasmasmentioning
confidence: 99%